Unwind : UnWholly - Book 2 - Shusterman, Neal. (New York : Simon & Schuster Books For Young Readers, 2012)
"Thanks to Connor, Lev, and Risa, and their high-profile revolt at Happy Jack Harvest Camp, people can no longer turn a blind eye to unwinding. Ridding society of troublesome teens and, in the same stroke, providing much- needed tissues for transplant might be convenient, but its morality has finally been brought into question. However, unwinding has become big business, and there are powerful political and corporate interests that want to see it not only continue, but expand, allowing the unwinding of prisoners and the impoverished. Cam is a teen who does not exist. He is made entirely out of the parts of other unwinds. Cam, a 21st century Frankenstein, struggles with a search for identity and meaning, as well as the concept of his own soul, if indeed a rewound being can have one. When a sadistic bounty hunter who takes "trophies" from the unwinds he captures starts to pursue Connor, Risa and Lev, Cam finds his fate inextricably bound with theirs"--
860L
Accelerated Reader AR
Keywords: Fugitives from justice; Juvenile fiction; Survival; Juvenile fiction; Revolutionaries; Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Fugitives from justice; Fiction; Survival; Fiction; Revolutionaries; Fiction; Identity; Fiction; Science fiction; Science fiction